The Adler grade by Doppler ultrasound is associated with clinical pathology of cervical cancer: Implication for clinical management. - Dehong Che; Zhirong Yang; Hong Wei; Xuedong Wang; Jiayin Gao (PLoS ONE, 2020)
OBJECTIVE:To analyze the relationship of Adler grade by transvaginal color Doppler flow imaging (TV-CDFI) and the clinical pathological parameters of patients with cervical cancer, and to identify the value of Adler grade in the diagnosis and treatment of cervical cancer. METHODS:Patients with cervical cancer diagnosed pathologically in our hospital from January 1, 2019 to December 31, 2019 were included, All patients underwent TV-CDFI examination, and the images were divided into 0 to III grades according to the Adler grades, and the correlations between the Adler classification and clinical pathological parameters (clinical stage, mass size, pathological type, squamous cell carcinoma subtype, CA125, CA199) were analyzed. RESULTS:A total of 162 patients with cervical cancer were included. With the increase of Adler severity, the clinical stage of cervical cancer increased accordingly. the cancer size differed significantly in patients with different Adler grade (p = 0.004); There were significant differences in the level of CA125, CA199 between the squamous cell carcinoma and adenocarcinoma (all p<0.05). the Adler grade was positively related with the clinical stage, pathological type and squamous cell carcinoma subtypes of cervical cancer (all p<0.05), no correlations were found among the Adler grade and the cancer size, CA125, CA199 (all p>0.05). The area under ROC curve of the cervical squamous cell carcinoma predicted by Adler grade based on FIGO results and pathological results was 0.811and 0.762 respectively (all p<0.05). CONCLUSIONS:Adler grades are closely associated with the clinical pathology of cervical cancer, which may be a convenient and effective approach for the assisting assessment of cervical cancer.